Deletion of Orphan G Protein-Coupled Receptor GPR37L1 in Mice Alters Cardiovascular Homeostasis in a Sex-Specific Manner - Mouat, Margaret A.; Jackson, Kristy L.; Coleman, James L. J.; Paterson, Madeleine R.; Graham, Robert M.; Head, Geoffrey A.; Smith, Nicola J. (Frontiers in Pharmacology, 2021)
GPR37L1 is a family A orphan G protein-coupled receptor (GPCR) with a putative role in blood pressure regulation and cardioprotection. In mice, genetic ablation of Gpr37L1 causes sex-dependent effects; female mice lacking Gpr37L1 (GPR37L1-/-) have a modest but significant elevation in blood pressure, while male GPR37L1-/- mice are more susceptible to cardiovascular dysfunction following angiotensin II-induced hypertension. Given that this receptor is highly expressed in the brain, we hypothesise that the cardiovascular phenotype of GPR37L1-/- mice is due to changes in autonomic regulation of blood pressure and heart rate. To investigate this, radiotelemetry was employed to characterise baseline cardiovascular variables in GPR37L1-/- mice of both sexes compared to wildtype controls, followed by power spectral analysis to quantify short-term fluctuations in blood pressure and heart rate attributable to alterations in autonomic homeostatic mechanisms. Additionally, pharmacological ganglionic blockade was performed to determine vasomotor tone, and environmental stress tests were used to assess whether cardiovascular reactivity was altered in GPR37L1-/- mice. We observed that mean arterial pressure was significantly lower in female GPR37L1-/- mice compared to wildtype counterparts, but was unchanged in male GPR37L1-/- mice. GPR37L1-/- genotype had a statistically significant positive chronotropic effect on HR across both sexes when analysed by two-way ANOVA. Power spectral analysis of these data revealed a reduction in power in the heart rate spectrum between 0.5-3 Hz in female GPR37L1-/- mice during the diurnal active period, which indicates that GPR37L1 / mice may have impaired cardiac vagal drive. GPR37L1 / mice of both sexes also exhibited attenuated depressor responses to ganglionic blockade with pentolinium, indicating that GPR37L1 is involved in maintaining sympathetic vasomotor tone. Interestingly, when these mice were subjected to aversive and appetitive behavioural stressors, the female GPR37L1-/- mice exhibited an attenuation of cardiovascular reactivity to aversive, but not appetitive, environmental stimuli. Together, these results suggest that loss of GPR37L1 affects autonomic maintenance of blood pressure, giving rise to sex-specific cardiovascular changes in GPR37L1-/- mice.